Thermal performance comparison of aluminum and iron alloys in heat exchangers for solar water heating systems: Experimental study under Iraqi climate conditions - Emad Jaleel Mahdi; Hussein Fawzi Hussein; Farqad Rasheed Saeed (Next Materials, 2025)
Solar water heating systems (SWHS) represent a critical technology for achieving global renewable energy targets, with the International Energy Agency projecting solar thermal could meet 17 % of worldwide heating demand by 2030. However, optimal material selection for heat exchangers in extreme climates like Iraq (4.4–44.5°C) remains unresolved, particularly for evacuated-tube systems. This study experimentally compares aluminum (Al) and iron (Fe) radiators in a closed-cycle SWHS under Iraqi conditions, evaluating thermal dissipation rates, fan-assisted airflow effects, and cost-performance tradeoffs. Using a controlled setup with evacuated tube collectors (300 L capacity, 5 L/min flow rate), performance was assessed through steady-state measurements (ΔT activation threshold: 8°C) and metallurgical analysis.Results demonstrate Al’s superior thermal conductivity (205 W/m·K) enables 28 % faster heat dissipation than Fe (80 W/m·K), achieving ΔT = 10°C in 35 versus 48 min. Fan integration further improves Al’s efficiency by 15 %, reaching 82 % thermal efficiency despite a marginal 5–8 % energy penalty. Corrosion resistance and lightweight properties favor Al, while Fe’s cost-effectiveness suits budget-constrained applications. These findings provide actionable insights for SWHS design in arid regions, balancing rapid heat delivery Al + fan) with economic viability (Fe). The study bridges material science and applied engineering, offering a framework for climate-specific SWHS optimization.